(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
During the years 1992-1993 sampling was carried out in several barns in different Italian regions to study the hay mites. On fresh material, only a few specimens of mites belonging to species which live on vegetation or ground were found. On the other hand, a complex and characteristic coenosis was observed in samples collected after 4 to 5 months of storage and in debris collected on the ground in the barns. 19 species of mycophagous, predator and detritivorous mites were found. The most important of the first group are the Astigmata Lepidoglyphus destructor (Schrank, 1781), Ctenoglyphus plumiger (Koch, 1835) and Tyrophagus longior Gervais, 1844, while the detritivorous ones are the Astigmata Ctenoglyphus canestrinii (Armanelli, 1887) and the Prostigmata Tydeus sp.. The most numerous predators are the Mesostigmata Androlaelaps casalis casalis Berlese 1886, the Prostigmata Cheyletus eruditus (Schrank, 1781) and Cheletomorpha lepidopterorum (Shaw, 1794). The biocoenosis of hay, which also causes respiratory allergies in man, is almost constant all over Italy, and very similar to that observed in the rest of Europe, demonstrating that it is independent of local conditions but connected to the characteristic environment of the barn.